Ready Player One Program Event Poster - Kansas State University, K-State First (Kansas State University. K-State First., 2013)
A poster advertising an author talk by Ernest Cline at Kansas State University on October 10, 2013. Ernest Cline's book "Ready Player One" was selected as the 2013-2014 common book.
Keywords: Ready Player One; Events; Engagement; Common reading program; First-year experience program; Promotional materials; Promotional materials